Apollonius of Rhodes' Argonauts and literary tradition - Caldas, Thais Evangelista de Assis (2009)
The aim of this paper is to investigate the Greek poetic tradition of the myth of Jason and Medea. This paper also analyzes the intertextual relationships between the Alexandrian Epic - represented by Apollonius of Rhodes' Argonauts - and the Homeric poems, Hesiod and Pindar and also the Euripidean tragedy Medea and the idylls of Theocritus XIII and XXII.